Implementasi Pendidikan Karakter Religius di SMP Hikmah Teladan Bandung - Abdillah, Asep; Syafe'i, Isop (Jurnal Pendidikan Agama Islam, 2020)
The development of information technology lately can harm the character of a nation. One creative effort to overcome this problem is the character in educational institutions. This study aims to determine the application of religious character education. This research uses a descriptive-analytic method with a qualitative approach. The location of the study was at Bandung Hikmah Exemplary Junior High School, the subjects of the study were the principal, curriculum waka, educators, and students. The results of his research are; (1) religious character values that are applied are spiritual values and insanity, (2) implementation is carried out by integrating learning with various activities in school, (3) the supporting factor is adherence to discipline, while the inhibiting factor is environmental differences association and the community environment, (4) the results of the implementation of religious character education can be seen from the existence of self-awareness in religion and show good academic results.